Glucocorticoid receptor single nucleotide polymorphisms are associated with acute crisis pain in sickle cell disease. (6th August 2018) - Jhun, Ellie H; Sadhu, Nilanjana; Yao, Yingwei; He, Ying; Molokie, Robert E; Wilkie, Diana J; Wang, Zaijie Jim
Aim: Pain in sickle cell disease patients is heterogeneous and genetic polymorphisms may predispose an individual to varied vulnerability to painful events. We studied the association of SNPs in the glucocorticoid receptor gene ( NR3C1 ) with pain in sickle cell disease.Method: Acute pain was scored as the number of utilizations due to crisis pain in a 12-month period. Chronic pain was calculated as the Composite Pain Index score.Results & conclusion: rs33389 T allele (IRR = 1.53, p = 0.014 additive; IRR = 1.64, p = 0.011 recessive), rs2963155 G allele (IRR = 1.80, p < 0.001 additive; IRR = 2.25, p = 0.021 dominant; IRR = 2.07, p < 0.001 recessive) and rs9324918 C allele (IRR = 1.43, p = 0.021 additive) were associated with higher utilization rates, indicating the potential contribution of NR3C1 polymorphisms to acute pain heterogeneity in sickle cell disease.